(untitled) (Journal of Bangladesh Institute of Planners, 2010)
Public buses in Dhaka City are inadequate in numbers and mostly remain over-crowded which is not accessible for many people, particularly the elderly or disabled and the women. Considering the travel problems of women, in the early 1980s Bangladesh Road Transport Corporation (BRTC) had provided services of ‘women only’ bus (called ‘women-bus’). However, the operation was stopped immediately after some days of its inauguration. Later on, in several times, BRTC initiated similar project but could not survive for various reasons. Lastly, again in July 2008, only 5 buses have been launched in one route for ‘women-only’ bus service. This paper explores the existing route, frequency, and service quality of the ‘women-only’ bus and investigates why this service could not survive in the past or lessons learnt from the previous failures. The ‘women-only’ bus service was observed and interviews of the passengers have been done for exploring the existing situation of the service whilst a Focus Group Discussion (GFD) was done for investigating transportation problems of women, their perception about ‘women-only’ bus service, and expectations about the service. The success of ‘women-only’ bus service may provide insights for expansion or improvement of the service, which in turn could help solving the transportation problems of women. Journal of Bangladesh Institute of Planners, Vol. 3, Dec 2010, pp. 17-32